Correlation and characteristics of self-rating and clinical rating of depression among alcoholics in the course of early abstinence - Mandić-Gajić Gordana; Samardžić Radomir; Špirić Željko (Vojnosanitetski Pregled)
Background/Aim. Depression is an alcoholism relapse risk factor, but frequently stays underdiagnosed among treated alcoholics. The correlation and characteristics of self-reported and clinically assessed depression in the course of early alcohol abstinence were explored. Methods. A total of 100 inpatient, primary male alcoholics (20-60 years) diagnosed according to Classificaton of Mental and Behavioural Disorders (ICD-10) and Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) were recruited consecutively. The Hamilton Depression Rating Scale (HDRS) and Beck Depression Inventory (BDI) were scored on admission (T1), after 4 weeks (T2) and after 8 weeks (T3). Student's t-test, repeated measures ANOVA and Pearson's correlation between the scores were done (p < 0.05). Factor analyses of symptoms were performed. Results: On HDRS T1, T2, T3 90,7%, 39.5%, 17.4% alcoholics were depressive, respectively. The mean HDRS vs BDI scores on T1, T2 and T3 were 15.16 ± 6.34, 7.35 ± 4.18, 4.23 ± 2.93 vs 14.20 ± 9.56, 8.14 ± 7.35, 5.30 ± 4.94, respectively. Depression severity significantly lowered in the course of abstinence (ANOVA). The HRDS and BDI correlations on T1, T2 and T3 were significant (r1 = 0.763, r2 = 0.684, r3 = 0.613 respectively). Dysphoric mood, anxious, vegetative and cognitive HDRS subscales on T1, T2 and T3 were detected, but not BDI factors, thus BDI symptoms were analysed. Conclusions. The majority of alcoholics had depression on admission. A predominant mild-degree with a significant lowering of depression severity and positive significant correlations between HRDS and BDI scores in the course of abstinence were detected. The dysphoric mood on the HDRS sub-scale, and self-blame, anhedonia and guilt BDI symptoms were most prominent and persisted. The BDI could be a useful tool not only for routine screening and reassessment of depression, but also for exploring emotional content during early abstinence and planning tailored integrative therapy and relapse prevention for alcoholics.